Perhitungan Oil Losses Pada Ampas Press di Proses Pengepresan Unit Screw Press PT. XYZ - Rosmiati Rosmiati; Dian Kurnia; Sorta Lumbantoruan (CV MEDAN TEKNO SOLUSI, 2024)
This research was conducted at PT. XYZ. Oil losses are the percentage of oil that is absent or not included in the subsequent oil processing process but is included in the waste process. The aim of this research is to determine the percentage of oil loss contained in press dregs using the soxhletation extraction method. Based on the results of mass balance calculations, it was obtained that the number of components entering the screw press was 22,401 kg/hour of digester chopping and 6000 kg/hour of delusion water. The number of components coming out of the Screw press, namely press dregs, is 8,400 kg/hour and Delution crude oil is 20,001 kg/hour. The results of this research show that the oil losses obtained during the pressing process were 4.45% or 373.80 kg/hour. This is in accordance with factory standards where oil losses are 4-6%.